Methods as Moving Ground: Reflections on the ‘Doings’ of Mobile Methodologies - Boas, Ingrid (2020)
As mobilities studies became a well-respected field in social science, discussions on mobile research designs followed. Usually, these discussions are part of empirical papers and reveal specific methodological choices of individual researchers, or groups of researchers sharing the same objectives and questions. This article starts with a different approach. It is based on continuous discussions between four researchers who developed their own version of mobility-driven projects, starting from different disciplinary backgrounds and using different research techniques. By sharing and contrasting personal fieldwork experiences, we reflect on the doings of mobile methodologies. We engage with the mistakes, dilemmas, and (dis)comforts that emerge from our own mobile research practices, and discuss what this implies for relations of power between the researcher and the research participants, and to what extent mobile research can represent the mobility that we seek to study. Specifically, the article addresses three questions: 1) To what extent do we produce different knowledge with our mobile methodologies? 2) How do our smooth writings about methodology relate to the ‘messy’ realities in the field? 3) How do our practices articulate and transcend difference between researchers and research participants?